Resilience of Mothers Who Have Down Syndrome Children in Sidoarjo - Fiqqi Anggun Lestari; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2015)
The aim of this study was to describe the characteristics and resilience factors for mothers who have children experiencing Down Syndrome. That is factors that help mother finds the strength to face the problem. The method was a qualitative exploratory study using three subjects 30-45 years old mother who has a child with Down syndrome and has resilience. The determination of the subject used purposive sampling techniques and located in some places according to the agreement of subject and significant others. Data collection methods used were interviews equipped with general guidelines as well as the recording field. The results showed that each mother were different in terms of characteristics and resilience factors and differences in educational factors, economic and employment background. Factors that affected the subject resilience also have differences. Some of the factors supporting emerging resilience, the family support factor was the support obtained by the subject.